(untitled) (Research, Society and Development, 2021)
The objective of this report of two cases of pregnancy-associated breast cancer (PBC) is to contribute to the theoretical empirical gap about the repercussions for the mother-child binomial, resulting from the association of cancer during pregnancy. Two breast cancer patients receiving doxorubicin, cyclophosphamide and docetaxel therapy were recruited for pharmacotherapeutic follow-up. Patient 1, 42 years old, 26 weeks pregnant, mixed race, street sweeper, mother of six, diagnosed with left breast cancer of the invasive ductal carcinoma (IDC), stage III-B, grade III, hormone receptor (RH) negative, HER-2 positive, with high blood pressure, smoker for 20 years with tobacconist, former alcoholic. Presented adverse drug reactions (ADR) during chemotherapy (CT): constipation; fatigue; hyperpigmentation; mucositis and anemia; hyperglycemia and increased alkaline phosphatase. Patient 2, 39 years old, 30 weeks pregnant, unemployed, mother of three, diagnosed with ICD-type right breast cancer, stage III-A, grade II, RH negative, HER-2 negative, triple negative, has a history of Immune thrombocytopenic purpura (ITP) and no social history of smoking or drinking. Presented ADR during QT: dry mouth; fatigue; change of taste; diarrhea; hyperpigmentation; anemia; hyperglycemia; increase in alkaline phosphatase and oxaloacetic transaminase (GOT). PBC is considered a challenging and rare event, although the incidence with delayed pregnancy beyond the age of 30 is increasing. In addition, the active participation of the multidisciplinary team focused on maternal-fetal well-being is important. In this study, the main ADR presented by the patients were mild, mainly gastrointestinal and biochemical.